National, regional, and urban-rural patterns in fixed-terrestrial broadband internet access and cardiac rehabilitation utilization in the United States - Erik H. Van Iterson; Luke J. Laffin; Leslie Cho (Elsevier, 2023)
Objective: Sparse patterns in fixed-terrestrial broadband internet access are predominantly observed among older adults and low income areas, which are interrelated factors also associated with low center-based cardiac rehabilitation (CR) utilization in the United States (US). Telehealth CR is proposed to increase CR utilization under an assumption that fixed-terrestrial broadband internet access is readily available nationwide and parallels CR utilization demand. We aimed to characterize national, geographical, and urban-rural patterns in fixed-terrestrial broadband internet access, CR eligibility rates, and center-based utilization throughout the US. Methods: Centers for Disease Control data were used to estimate CR eligibility rates and center-based utilization for 2017-2018 among Medicare fee-for-service beneficiaries aged ≥65 years. Census Bureau data for 2018 were used to estimate fixed-terrestrial broadband internet access among households of adults aged ≥65 years. Results: Southern states exhibited the highest percentage of households without broadband internet [median (IQR): 32% (24-39)] coupled with the highest CR eligibility rates [per 1,000 beneficiaries, median (IQR): 18 (15-21)] and lowest participation rates [percentage completing ≥1 session, median (IQR): 25% (17-33)]. Compared with urban areas, rural areas demonstrated significantly higher eligibility rates [15.5 (13.2-18.4) vs. 17.4 (14.5-21.0)], participation rates [30.6% (22.0-39.4) vs. 34.6% (22.6-48.3)], and percentage of households without broadband internet [23.8% (18.1-29.2) vs. 31.6% (26.5-37.6)], respectively. Conclusion: Overlapping patterns in fixed-terrestrial broadband internet access and CR eligibility rates and center-based utilization suggest telehealth CR policies need to account for the possibility that lack of broadband-quality internet access could be a barrier to accessing telehealth CR delivery models.